Headache in Pregnancy: An Approach to Emergency Department Evaluation and Management - Schoen, Jessica C. (West J Emerg Med, 2015)
Headache is a common presenting complaint in the emergency department. The differential diagnosis is broad and includes benign primary causes as well as ominous secondary causes. The diagnosis and management of headache in the pregnant patient presents several challenges. There are important unique considerations regarding the differential diagnosis, imaging options, and medical management. Physiologic changes induced by pregnancy increase the risk of cerebral venous thrombosis, dissection, and pituitary apoplexy. Preeclampsia, a serious condition unique to pregnancy, must also be considered. A high index of suspicion for carbon monoxide toxicity should be maintained. Primary headaches should be a diagnosis of exclusion. When advanced imaging is indicated, magnetic resonance imaging (MRI) should be used, if available, to reduce radiation exposure. Contrast agents should be avoided unless absolutely necessary. Medical therapy should be selected with careful consideration of adverse fetal effects. Herein, we present a review of the literature and discuss an approach to the evaluation and management of headache in pregnancy